Comparative Study on Legal Certainty of Consumer Protection Regarding E-Commerce Transactions, Between Indonesia, India and the United States - Diana Desiree Hardigaluh; M Sofyan Pulungan (Musamus Law Review, 2022)
In both conventional and electronic buying and selling agreements, the protection of consumer rights should be the main concern of business actors. Although there are already regulations governing consumer protection, until now there are still frequent violations of consumer rights, especially in e-commerce transactions. This article is juridical-normative research that compares the laws and regulations concerning consumer protection law in e-commerce transactions between Indonesia, India, and the United States. Through comparative studies and analysis using data sources from the literature, this study explores how the legal certainty of consumer protection in e-commerce transactions in Indonesia is being achieved. In addition, this research also describes the comparison regarding the legal certainty of consumer protection in e-commerce transactions in Indonesia between India and the United States based on the United Nations Guidelines for Consumer Protection. Furthermore, this study provides a prescription for how the legal certainty of consumer protection in e-commerce transactions in Indonesia should be when viewed from a comparison of consumer protection laws in e-commerce transactions in India and the United States.